Dissemination of adobe technology in a housing reconstruction program - Vargas Neumann, Julio (1986)
This paper describes a housing reconstruction program in northern Peru after the 1983 floods due to the "El Niño" phenomenon. The objective of this program was to implement and disseminate improved adobe construction technologies through instruction, training, and technical assistance in rural communities that were relocated after the floods. This project was carried out as the field dissemination part of the Research Project "Preservation of Adobe Constructions in Seismic and Rainy Areas," developed by the Catholic University of Peru (PUCP) from June 1984 to May 1985.